Pelatihan Penyelenggaraan Jenazah di Kelurahan Tubajeng Kecamatan Bajeng Kabupaten Gowa - M. Kasim; Islahuddin Gunawan; Sirajuddin Sirajuddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
PkM in the form of training on organizing the funeral which was carried out in the Tubajeng Village aims to provide insight to the Muslim community about the procedures for organizing the funeral according to the guidance of the Prophet. The method used in this activity combines lecture, demonstration and practice methods. This activity has shown encouraging initial results in the form of participants' understanding of the procedures for organizing the funeral according to the guidance of the Prophet.